Pengaruh Green Brand Awareness terhadap Repurchase Intention dengan Mediasi Green Trust dan Moderasi Green Product Knowledge pada Hejau Detergent Sheets - Lulu Alya Rudiyanto; Dede Kurnia; Nizza Nadya Rachmani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Public awareness of environmental issues has led to the emergence of environmentally friendly product innovations, one of which is Hejau Detergent Sheets, the first paper detergent in Indonesia. Although it offers environmental and practical benefits, this product still faces challenges in the form of low brand awareness and consumer understanding, which affect trust and repurchase intention. This study aims to analyze the influence of green brand awareness on repurchase intention, with green trust as the mediating variable and green product knowledge as the moderating variable. The study employs a quantitative method with a descriptive-inferential approach. The sampling technique is purposive sampling, targeting consumers who have previously used the Hejau product. The sample size was determined using Slovin's formula, resulting in 181 respondents. Data were collected through an online questionnaire and analyzed using a moderated mediation model (Model 7 PROCESS Macro Hayes). The results of the study indicate: (1) green brand awareness significantly influences green trust (coefficient 1.31); (2) green trust significantly influences repurchase intention (coefficient 0.81); (3) green brand awareness significantly influences repurchase intention (coefficient 0.34); (4) green trust mediates the influence of green brand awareness on repurchase intention; and (5) green product knowledge moderates the influence of green brand awareness on green trust.